A quantitative LC–MS/MS method for the determination of tissue brincidofovir and cidofovir diphosphate in a MuPyV‐infected mouse model. (14th January 2021) - Guzman, Bryan B.; Schauer, Amanda P.; Dunn, John A.; Cottrell, Mackenzie L.; Sykes, Craig
Abstract: Brincidofovir (BCV) is an investigational lipid conjugate of the nucleotide analog cidofovir (CDV), which is being developed as a medical countermeasure for the treatment of smallpox. BCV is active against double‐stranded DNA viruses including BK and JC viruses. Here, we validated procedures for quantifying BCV and its pharmacologically active moiety cidofovir diphosphate (CDV‐PP) in mouse kidney, brain and spleen tissue homogenates. Following homogenization, BCV and CDV‐PP were extracted from the tissues by protein precipitation with their stable, isotopically labeled internal standards, BCV‐d6 and 13 C3 15 N2 ‐CDV‐PP. Then, samples were analyzed for BCV by reverse‐phase chromatography on a Waters Xterra MS C18 (50 × 2.1 mm, 3.5 μm particle size) column while CDV‐PP was analyzed on a Thermo BioBasic AX (50 × 2.1 mm, 5 μm particle size) column using anion exchange chromatography. Detection was achieved by electrospray ionization in positive ion mode on an AB Sciex API‐5000 triple quadrupole mass spectrometer. The calibration curves were linear over a range of 1.00–1, 000 ng/ml homogenate and 0.050–50.0 ng/ml homogenate for BCV and CDV‐PP, respectively. These methods were validated according to US Food and Drug Administration guidance for industry and may be used to characterize the tissue pharmacology of both analytes to advance its preclinical development.